2022
DOI: 10.1002/cncr.34338
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum impairs DNA mismatch repair and stability in patients with squamous cell carcinoma of the head and neck

Abstract: Background Dysbiosis of the laryngeal microbiota has been demonstrated to the development of head and neck squamous cell carcinoma (HNSCC), but the association of Fusobacterium and Fusobacterium nucleatum (F. nucleatum) with DNA mismatch repair (MMR) and microsatellite instability (MSI) has not been investigated. Methods The abundance of Fusobacterium and F. nucleatum, the status of deficient MMR (dMMR) and MSI, and MMR‐related gene expression were analyzed in 171 HNSCC tissues, 61 paired para‐tumor tissues, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Our findings support recent observations that higher tumoral levels of F. nucleatum were associated with better clinical outcomes in patients with head and neck cancers (Chen et al 2020 ; Neuzillet et al 2021 ). In contrast, one study showed that a higher abundance of F. nucleatum predicted recurrence and shorter disease-free survival in patients with laryngeal cancer (Hsueh et al 2022 ). This disagreement between studies may, however, result from variations in the tumor microenvironment between the larynx and oral cavity.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings support recent observations that higher tumoral levels of F. nucleatum were associated with better clinical outcomes in patients with head and neck cancers (Chen et al 2020 ; Neuzillet et al 2021 ). In contrast, one study showed that a higher abundance of F. nucleatum predicted recurrence and shorter disease-free survival in patients with laryngeal cancer (Hsueh et al 2022 ). This disagreement between studies may, however, result from variations in the tumor microenvironment between the larynx and oral cavity.…”
Section: Discussionmentioning
confidence: 98%
“…Fusobacterium species in metastatic tumours are highly similar to those found in primary tumours, suggesting that the microbiota maintains stability between primary and metastatic tumours [18]. Reportedly, F. nucleatum is significantly increased in patients with lymph node metastasis and F. nucleatum upregulates keratin 7-antisense/keratin 7 (KRT7-AS/KRT7) through the nuclear factor kappa B pathway and promoted CRC cell migration [19]. F. nucleatum regulates the TLR4/MYD88/miR-205–5 p pathway and induces epigenetic alterations, thus promoting DNA damage and cell proliferation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, F. nucleatum is significantly increased in patients with lymph node metastasis and F. nucleatum upregulates keratin 7-antisense/keratin 7 (KRT7-AS/KRT7) through the nuclear factor kappa B pathway and promoted CRC cell migration [19]. F. nucleatum regulates the TLR4/MYD88/miR-205–5 p pathway and induces epigenetic alterations, thus promoting DNA damage and cell proliferation [19]. F. nucleatum induces the epithelial–mesenchymal transition (EMT) by regulating the long non-coding RNA MIR4435-2HG [20].…”
Section: Discussionmentioning
confidence: 99%
“…Fusobacteria at the treatment baseline was correlated with nonresponders [18]. Changes in the oral epithelium in vivo are strongly related to Socransky's red complex bacteria [19], mainly Porphyromonas gingivalis [14,20,21], Porphyromonas catoniae [22], and Fusobacterium nucleatum [23,24], for their immune-receptor upregulation and tight junction degradation capacity [25].…”
Section: Head and Neck Cancermentioning
confidence: 99%